IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM UPAYA PENINGKATAN MUTU PEMBELAJARAN MATA PELAJARAN AQIDAH AKHLAK DI SMPIT FAJAR ILAHI KECAMATAN BATU AJI KOTA BATAM - Imam Sayuti ,; Sri Rahayu Ningsih, (UNISAN JURNAL, 2024)
Education plays a highly strategic role in shaping the character and morals of the younger generation. In the context of Islamic education, the subject of Aqidah Akhlak holds a crucial role in building the foundations of faith and noble behavior in accordance with Islamic teachings. Therefore, efforts to improve the quality of Aqidah Akhlak education are vital. This research aims to describe the implementation of school-based management in efforts to improve the quality of Aqidah Akhlak education at SMPIT Fajar Ilahi, Batu Aji District, Batam City. The research method used is qualitative research with a case study approach. Data were collected through observation, in-depth interviews, and documentation. The research participants consisted of the principal, teachers, and students. The research results show that the implementation of school-based management at SMPIT Fajar Ilahi involves various aspects, such as structured planning, implementation, and evaluation. The principal plays a significant role in leading and directing quality improvement programs, including teacher training, curriculum development, and the provision of adequate facilities and infrastructure. Aqidah Akhlak teachers are also actively involved in developing innovative teaching methods that meet the needs of students. Additionally, support from parents and the community contributes to creating a conducive learning environment. The success of school-based management implementation at this school is evident from the increase in students' academic and non-academic achievements, as well as the enhanced motivation and participation of students in the learning process. This research concludes that school-based management is effective in improving the quality of Aqidah Akhlak education at SMPIT Fajar Ilahi. The recommendations proposed include increasing teacher capacity through continuous training, strengthening cooperation with external parties, and developing a comprehensive evaluation system